Developing expenditure questions: Findings from focus groups - Jo d'Ardenne; Margaret Blake (Institute for Fiscal Studies (IFS), 2012)
Currently there is no established way to measure expenditure in the context of a general purpose survey. Therefore NatCen's Questionnaire Development and Testing (QDT) Hub, working in collaboration with the Institute for Fiscal Studies and collaborators from Oxford and Cambridge Universities, are looking at how best to measure expenditure in a social survey context. This report provides findings from a series of focus groups investigating how people think about household expenditure and what issues people may have in reporting household expenditure in a social survey context. The information collected in the focus groups will be used as a starting point for designing new questions on household spending for use in future social surveys. Subsequent stages of work will include cognitively testing any new questions produced and consulting a panel of experts over the proposed questions. This project was funded by the Nuffield Foundation.
Keywords: 330